Serum vitamin D level – the effect on the clinical course of psoriasis - Bergler-Czop, Beata; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Psoriasis is a hyperproliferative disorder of the skin, and vitamin D analogs are widely used in its treatment. It is evident that ultraviolet radiation enables vitamin D3 (cholecalciferol) formation in the epidermis, and this product is further converted into the active metabolites 25-hydroxycholecalciferol and 1,25-hydroxycholecalciferol, which exert several important effects on the skin. The disruption in proper functioning of the skin which occurs in psoriasis leads to a loss of capacity for cutaneous synthesis of vitamin D3. In consequence, it activates a vicious circle that impairs homeostasis of the skin and results in a progressive decrease in the level of vitamin D in the whole human body. Aim: To estimate the prevalence of vitamin D serum deficiency in patients with psoriasis and analyse the association of vitamin D food intake with clinical features. Material and methods : Forty adults with psoriasis and 40 healthy subjects (control group) were recruited. Psoriasis plaques were diagnosed and evaluated by the PASI scale. Collected blood samples enabled measurement of serum vitamin D level by assessment with the immunoenzyme technique. Results: The analysis with the Mann-Whitney U test revealed a statistically significant difference in 25-hydroxycholecalciferol level between healthy individuals and patients with psoriasis (p = 0.048). In both groups (control and psoriatic) the level of 25-hydroxycholecalciferol was seriously deficient (< 50 nmol/l). There was also a negative correlation of 25-hydroxycholecalciferol serum level with both PASI (r = –0.43) and the duration of psoriasis (r = –0.53). Conclusions : It is necessary to bear in mind that not only the ingestion of food rich in vitamin D is necessary, but also the production of vitamin D with sun exposure. The quantity of 25-hydroxycholecalciferol is very important both in the general population and in patients with psoriasis, because these groups have a distinct metabolism.